The Effectiveness of Corporate Social Responsibility in Mediating the Effect of Total Assets and Inventory Turnover on Company Value (Empirical Study in Food & Beverage Company on the Indonesia Stock Exchange) - Nadya Budiarti; Siti Istikhoroh; Mutiara Rachma Ardhiani (International Journal of Economics, Business and Innovation Research, 2023)
This studies became carried out to recognize the impact of general belongings and stock turnover on company price with CSR as a mediating variable in food & beverage sub-region businesses at the IDX. A general of thirteen businesses have been protected withinside the pattern decided on the usage of a purposive sampling approach for the 2019–2021. The records evaluation approach used is course evaluation. The effects of this studies show that general property and stock turnover haven't any impact on organisation value. While CSR has a power on corporation value. Total property and stock turnover haven't any impact on CSR. CSR does now no longer mediate the impact of general property on corporation value. CSR does now no longer mediate the impact of stock turnover on organisation value.